Modelling and analysis of the supraspinatus tendon: a finite element approach (2011)
Supraspinatus tendon tearing is one of the most common injuries of the rotator cuff. This tearing produces pain and reduces the mechanical performance of the tendon; therefore, it reduces the functionality of the shoulder. A finite element model of the supraspinatus tendon, modelled as a transversely isotropic hyperelastic material, allows quantifying the effect of a tear on the load-bearing capacity of the tendon by means of a strength index. Comparing the strength index value with a given physiological force, it is possible to calculate a critical tear size that works a clinical criterion for surgical prescription. The critical tear size is determined when the insertion can no longer with stand the forces that are applied during normal activities and, therefore, the effect of the variation of the physiological force on the critical tear size is investigated.